2019
DOI: 10.1177/1071100719867937
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and Distal Failure Site Analysis in Percutaneous Achilles Tendon Rupture Repair

Abstract: Background: Different techniques have been described for percutaneous Achilles tendon rupture repair, but no biomechanical evaluation has been performed separately for proximal and distal suturing techniques. The purpose of this study was to biomechanically analyze proximal versus distal percutaneous Achilles suture configurations during cyclic loading and load to failure. Methods: A simulated, midsubstance rupture was created 6 cm proximal to the calcaneal insertion in fresh-frozen cadaveric Achilles tendons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Hockenbury found percutaneous repair of Achilles tendon ruptures provided approximately 50% of the initial strength afforded by open repair [ 25 ]. Wagner [ 33 ] reported that the distal fixation site in this Achilles tendon repair with a triple nonlocking technique was significantly weaker than the proximal fixation site with a triple locking technique, a Bunnell-type technique, or a double Bunnell-type technique, the constructs tested were not strong enough to confidently allow weight-bearing in a walker boot. Patel [ 13 ] and Wagner [ 34 ] placed the proximal sutures into the calcaneus with a Push Lock anchor system to overcome this disadvantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hockenbury found percutaneous repair of Achilles tendon ruptures provided approximately 50% of the initial strength afforded by open repair [ 25 ]. Wagner [ 33 ] reported that the distal fixation site in this Achilles tendon repair with a triple nonlocking technique was significantly weaker than the proximal fixation site with a triple locking technique, a Bunnell-type technique, or a double Bunnell-type technique, the constructs tested were not strong enough to confidently allow weight-bearing in a walker boot. Patel [ 13 ] and Wagner [ 34 ] placed the proximal sutures into the calcaneus with a Push Lock anchor system to overcome this disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors didn't meet re-rupture [ [30] , [31] , [32] ]. Clanton [ 36 ] and Wagner [ 33 ] found that percutaneous techniques elongated the Achilles tendon 10 mm. Wagner [ 33 ] recommended pre-tensioning the repair.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Achilles tendon needs to sustain a minimum of 190 N over repeated load cycles and glide 4 cm during the normal gait cycle. 8 , 17 , 22 Unfortunately, combined tendon and soft tissue injuries ultimately yield some degree of impairment, even with current methods of composite flap single-stage reconstruction. There can be wide variations in torque loss, ranging from 6.0% to 80.0% differences between injured and uninjured limbs, in patients undergoing composite flap reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical features are not consistent among different sections of the Achilles tendon and may contribute to results of the common rupture site. 16 Different biomechanical strengths may be related to various arrangement patterns of type I and type III collagens. Ruptured Achilles tendons have more type III collagens than healthy Achilles tendons, and this pathological feature is evident in regions adjacent to the rupture site.…”
Section: Discussionmentioning
confidence: 99%